State of injury: liberal multiculturalism and the Muslim subject after prison. Issue 4 (20th October 2021) - Williams, Ryan
ABSTRACT: The liberal political project has come under scrutiny for its unfulfilled promises of freedom and equality for those at the margins of society. This contribution approaches the critical analysis of state-citizen relations through inquiring into how liberal secular governance enables, limits, and reshapes moral and ethical potentialities. It draws on a study of Muslim men under probation supervision in East London and their relationships with their empathetic probation officers to show how the state can direct Muslim-citizen subjects in virtuous and restorative ways but also in ways that mark 'injury', directing subjectivities towards cooperation with exclusionary state practices. Taking an intersectional approach and through attention to pain, this contribution argues that the state is intimately invested in subject formation, but its effects are uneven and polarised according to its own sovereignty and governing logics. The uneven subjectivities reflect the 'precarity' of governing Muslims at the margins directed towards inclusion and exclusion, assisting and controlling, care and punishment.